2010
DOI: 10.1152/ajpregu.00706.2009
|View full text |Cite
|
Sign up to set email alerts
|

Role of urotensin II in health and disease

Abstract: Urotensin II (UII) is an 11 amino acid cyclic peptide originally isolated from the goby fish. The amino acid sequence of UII is exceptionally conserved across most vertebrate taxa, sharing structural similarity to somatostatin. UII binds to a class of G protein-coupled receptor known as GPR14 or the urotensin receptor (UT). UII and its receptor, UT, are widely expressed throughout the cardiovascular, pulmonary, central nervous, renal, and metabolic systems. UII is generally agreed to be the most potent endogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 151 publications
1
107
0
9
Order By: Relevance
“…Data are expressed as meanGS.E.M. AngII and losartan were co-administered to the piglets w10 min after intrarenal arterial bolus injection of losartan Ross et al 2010, Tsoukas et al 2011. However, the cyclic hexapeptide sequence in UII carboxyl-terminus, which is responsible for its biological activity, is highly conserved between species (Itoh et al 1987, Conlon et al 1990, Coulouarn et al 1998, Douglas et al 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data are expressed as meanGS.E.M. AngII and losartan were co-administered to the piglets w10 min after intrarenal arterial bolus injection of losartan Ross et al 2010, Tsoukas et al 2011. However, the cyclic hexapeptide sequence in UII carboxyl-terminus, which is responsible for its biological activity, is highly conserved between species (Itoh et al 1987, Conlon et al 1990, Coulouarn et al 1998, Douglas et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…These results raise the possibility that the hypotensive effect of urantide may be due to its systemic but not localized renal vasoregulatory actions. Neurons of the brain and spinal cord express UII (Coulouarn et al 1998, Douglas et al 2004, Ross et al 2010. Studies have also shown that UII can modulate cardiovascular homeostasis via central neural mechanisms (Gibson et al 1986, Lu et al 2002, Lin et al 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All functional data relate to UTS2R1, the single UTS2R receptor present in placental mammals, as the other UTS2R isoforms have only been obtained recently. UTS2R1 was originally described as being coupled to Gq, but other signal transduction pathways involving G s and G i have subsequently been identified, associated with multiple signaling cascades (Ross et al 2010).…”
Section: Uts2r5mentioning
confidence: 99%
“…Evidence points to the vasodilatation theory as a more tangible explanation for the development of HRS. Urotensin II (U II) is a somatostatinlike cyclic peptide, its vascular tone both species specific and diseases specific [6]. Urotensin II interfere with sympathetic and nitric oxide (NO) system [7].…”
Section: Introductionmentioning
confidence: 99%